THE EFFECT OF GREEN ACCOUNTING AND GREEN INVESTMENT ON FINANCIAL PERFORMANCE OF MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN THE 2020-2024 PERIOD - Hasanah, Nurul; Zurrahman, Finda Intan (AGUSPATI Research Institute, 2026)
This study aims to analyze the effect of green accounting and green investment on the financial performance of mining companies listed on the Indonesia Stock Exchange for the period 2020-2024. This study uses a quantitative approach with panel data regression methods. The research sample consisted of 20 companies selected through purposive sampling from a total of 39 mining companies. The data used was secondary data sourced from annual reports and sustainability reports. The results of the study indicate that green accounting does not have a significant effect on financial performance as proxied by Return on Assets (ROA), while green investment has a significant effect on ROA. Simultaneously, green accounting and green investment have a significant effect on company financial performance. These findings support stakeholder theory, signaling theory, and legitimacy theory in explaining the relationship between environmental practices and company financial performance.